An Analysis of Digital Library Publishing Services in Ukrainian Universities - Kolesnykova, Tetiana; Matveyeva, Olena (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective – The objective of this study was to assess the current state of digital library publishing (DLP) in university libraries in the Ukraine. The study was conducted in the hopes of gaining a better understanding of the DLP landscape, namely institutional operations, as well as their varying publishing initiatives, processes, and scope.Methods – The current study was conducted from January to June 2017 using a mixed methods approach, involving semi-structured interviews and an online questionnaire. Semi-structured interviews were conducted (n = 11) to gain insight into participants’ experiences with DLP. The interviews helped in the creation of the questions included in our online questionnaire. The questionnaire was distributed to 195 representatives (directors and leading specialists) of university libraries in the Ukraine. Replies were received from 111 of those institutions. The questionnaire consisted of 11 open- and closed-ended questions to allow the researchers to obtain a holistic picture of the process under investigation.Results – Analysis of the 111 questionnaires showed that for 26 libraries, DLP services were performed by employees of a separate structural unit of the library. For 34 libraries, employees of various departments were involved in performing certain types of services. The other 40 respondents’ libraries were planning to do this in the near future. Only 11 respondents replied that they did provide DLP services now nor planned to in the future. Among the libraries providing DLP services, the following results were observed: 54 of 60 work with digital repositories, 47 provide digital publishing platforms for journals, 26 provide digital publishing platforms for books, and 23 provide digital publishing platforms for conferences.Conclusions – The results obtained indicate a growing trend of expanding digital services in university libraries to support study, teaching, and research. Despite the still spontaneous, chaotic, and poorly explored nature of the development of the library publishing movement in the university libraries of the Ukraine, the readiness of librarians to implement publishing activities is notable. At the same time, the survey results point to specific aspects, such as organizational, economic, personnel, and motivational, that require further study.